2020
DOI: 10.1109/access.2020.3014501
|View full text |Cite
|
Sign up to set email alerts
|

Human-Robot Cooperation for Surface Repair Combining Automatic and Manual Modes

Abstract: This article develops a human-robot cooperation to carry out treatments such as sanding, polishing, etc. on the surface of a known rigid object. For this purpose, a vision system is considered to get the object location to ensure not only the perpendicularity of the robot tool to the object surface but also a smooth approach of the tool to the surface. In order to add flexibility, the proposal includes the simultaneous combination of automatic and manual modes of operation. Thus, the human user can guide the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In this new human in-theloop architecture, the whiteboard and eraser will be moved around freely, until the tool makes contact with some object. Then, a low-level controller enters the loop to regulate the force applied by the manipulator, as was done in [67]. This guarantees that certain constraints are not violated, such as upper/lower bounds of the applied force or the alignment between both surfaces in contact.…”
Section: Improvement Of Guimentioning
confidence: 99%
“…In this new human in-theloop architecture, the whiteboard and eraser will be moved around freely, until the tool makes contact with some object. Then, a low-level controller enters the loop to regulate the force applied by the manipulator, as was done in [67]. This guarantees that certain constraints are not violated, such as upper/lower bounds of the applied force or the alignment between both surfaces in contact.…”
Section: Improvement Of Guimentioning
confidence: 99%
“…In recent years, HRC has gained much research interest for enabling robots to perform complex operations by learning human skills [4], which has a wide range of applications such as surgeries [5], [6], assembly [7], and surface repair [8], [9]. Many automotive companies including Audi, Skoda, and Nissan have been using HRC methods via deployed cobots due to their affordability, built-in safety, and intuitive user interfaces (UIs) [2].…”
Section: Introductionmentioning
confidence: 99%
“…It must be noted that this chapter corresponds to two published contributions: (García et al, 2020) and (García et al, 2021). Where (García et al, 2021) contributes with a expansion of (García et al, 2020)] with the addition of a boundary constraint to the control scheme.…”
Section: Objectivementioning
confidence: 99%
“…It must be noted that this chapter corresponds to two published contributions: (García et al, 2020) and (García et al, 2021). Where (García et al, 2021) contributes with a expansion of (García et al, 2020)] with the addition of a boundary constraint to the control scheme. This being the case, this chapter is mostly based on (García et al, 2021), although the results from both applications are shown in the corresponding section.…”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation